Hyperreality on Onlineshop: Shopaholic Generation in Indonesia - Awalia, Hafizah (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
Shopping as the lifestyle in Indonesian society has been changed to post-modern era. The shopping moved from retail store or regular shop to online shop. Many online-shop sites, like Mataharimall.com, Tokopedia.com, Blibli.com, Lazada.com, Bukalapak.com, and Elevenia.com make Indonesian society become a shopaholic. The online shop served complete and cheaper goods than the retail shop. Some unique parts are electronics, outfits, even aeroplane tickets and tour packets will be ready in the online shop. The update data mentioned that E-Commerce in Indonesia reached US1.1 billion. Those are the bigger achieved of Indonesia than Singapore and Thailand in ASEAN (Data by Euro monitor, 2015). Now, Indonesian society entered the new paradigm of consumption. Not only what goods will be consumed, but also how to consume those products. The sensation of shopping, in reality, has been changed with shopping in hyper-reality (virtual world). Today, in Indonesia shopping is not about our needs, but to fulfil our desire. In the postmodern era, the production factor is not a significant factor, but the consumption factor can control the peopleâ€™s life. The bigger control handled by online media, like Instagram, Facebook and many others. The media can create the attractive display of shop, and it makes shopping lovers a shopaholic. Symbols, signification, codes are relevant in the consumerism era. Therefore, Baudrillard theory about consumptive society became approach and method for this research. The theory will analyse how the online shop as the online media reconstruct Indonesian society became a shopaholic and how the game of symbols, signs, and codes create consumptive behaviour in online shopping. Analysis units of this research are consumptive behaviour and online shop media in Indonesia.Â Â Keywords: Online Shop, Hyperreality, Shopaholic